High temperature oxidation and corrosion behaviour of titanium aluminide alloy Ti-52.5AI-10.0Ni-0.2Ru (at.%) - Mantyi, Hadio Caprice (My University, 2016)
The alloys Ti-52.5Al-10.0Ni (at.%) and Ti-52.5Al-10.0Ni-0.2Ru (at.%) were made by mixing, and melting their powders in a button arc furnace under an argon atmosphere. The high temperature oxidation and room temperature corrosion of behaviour of the alloys was investigated. Isothermal oxidation in air at 950°C for 120 hours and 720 hours was done. Cyclic oxidation behaviour of the alloys was also investigated in air and in a hot salt (Na2SO4) environment. The corrosion tests were conducted in 5 wt% and 25 wt% HCl. All the samples were characterised using scanning electron microscopy with energy dispersive X-ray spectroscopy, X-ray diffraction and hardness measurements. On solidification, the Ti-52.5Al-10.0Ni (at.%) alloy formed dendrites of γ-TiAl (~55 at.% Al) surrounded by a eutectic of γ-TiAl + Ti2NiAl3 (τ3) phases. Most of the nickel was found in the Ti2NiAl3 (τ3) phase (~12 at.%) with trace amounts in the dendrites (~0.5 at.%). The Ti-52.5Al-10.0Ni-0.2Ru (at.%) alloy formed dendrites of γ-TiAl (~53 at.% Al) surrounded by a eutectic of γ-TiAl + Ti2NiAl3 (τ3). Most of the nickel (~15 at.%) and ruthenium (~0.3 at.%) were in solid solution in the Ti2NiAl3 (τ3) phase, although small amounts of both metals were present in the dendrites (~1 at.% Ni and 0.1 at.% Ru). Under isothermal oxidation conditions, both alloys showed good oxidation resistance with a low mass gain (< 2%). The alloys formed a continuous scale of TiO2 and Al2O3 with good adherence to the substrate, but as exposure time increased, the scale was severely degraded and exfoliated from the surface. Cyclic oxidation conditions were more aggressive for both alloys. The Ti-52.5Al-10.0Ni-0.2Ru (at.%) alloy was more resistant and formed a nickel-rich sub-surface zone between the substrate and intermixed oxide layer. Both alloys had a fairly good corrosion resistance in HCl due to the presence of nickel. They formed a thin and non-continuous Al2O3 oxide scale on the surface of the γ-TiAl dendrites, with Ti3NiAl2O on the γ-TiAl + Ti2NiAl3 (τ3) eutectic regions. The acid mainly corroded the τ3 phase, thus attacking the eutectic and leaving the γ-TiAl dendrites exposed.
A dissertation submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Science in Engineering 15 October 2016
Keywords: Alloys--Corrosion; Metals--Effect of high temperatures on; Oxidation; Corrosion and anti-corrosives